'Word play' in the Ramesside Dream Book - Kasia Szpakowska (Studien zur Altägyptische Kultur, 2006)
Word play has long been acknowledged as a common feature in ancient Egyptian texts. This article offers an examination of word play in one divinatory text: the Ramesside Dream Manual (P.Chester Beatty III, r. 1-11). While scholars have noted some examples of word play in conjunction with sociological and philological analyses of the Dream Manual, the phenomenon has not been studied in depth. This investigation offers a typology for word play in the Dream Manual by examining it in the light of ancient Near Eastern word play generally. It also provides an inventory of and commentary on the relevant passages that contain word plays and an analysis of the various functions the device has in the Manual. It is the authors' hope that the study will provide a model for the systematic analysis of word plays in other Egyptian texts.